Transients due to multiple prestrike phenomenon when energizing capacitor banks with a vacuum circuit breaker - Barbieri, María Beatriz (2006)
The phenomenon of multiple prestrikes of the arc was observed in field measurements of the energization of a single 4.8 MVAR, 13.2 kV capacitor bank. This paper presents field measurements records and the results of the computer simulation of the transients when energizing the capacitor bank, made with the objective to calculate the overvoltages generated in remote points. A method to avoid the phenomenon is proposed.